2012
DOI: 10.1603/ec11150
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Evidence of Formosan Subterranean Termite (Isoptera: Rhinotermitidae) Colony Survivorship After Prolonged Inundation

Abstract: Levee breaches because of Hurricane Katrina in 2005 inundated 80% of the city of New Orleans, LA. Formosan subterranean termites were observed actively foraging within in-ground monitoring stations within months after this period of flooding. It was unknown if the activity could be attributed to preexisting colonies that survived inundation or to other colonies surviving flooding by being located at higher elevations readily invading these territories. Genotypic profiles of 17 termite colonies collected from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In our study, termites had access to the air in the release chamber and sand-free space, which may have contributed to their survival over 28 days. Previous studies showed that C. formosanus colonies could survive in hypoxic environments after prolonged flooding (up to 3 wk) by remaining in pockets of trapped air in their nesting system (Osbrink et al 2008, Owens et al 2012, Cottone et al 2015). Forschler and Henderson (1995) found that, when workers were submerged in water without air contact, they entered a state of quiescence with median lethal times of 11.1 h for C. formosanus and 19.6 h for R. flavipes .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, termites had access to the air in the release chamber and sand-free space, which may have contributed to their survival over 28 days. Previous studies showed that C. formosanus colonies could survive in hypoxic environments after prolonged flooding (up to 3 wk) by remaining in pockets of trapped air in their nesting system (Osbrink et al 2008, Owens et al 2012, Cottone et al 2015). Forschler and Henderson (1995) found that, when workers were submerged in water without air contact, they entered a state of quiescence with median lethal times of 11.1 h for C. formosanus and 19.6 h for R. flavipes .…”
Section: Discussionmentioning
confidence: 99%